2015
DOI: 10.17221/498/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fluoride in Antarctic krill (Euphausia superba) using ion chromatography and its pretreatments selection

Abstract: A rapid, sensitive and reliable method to quantify fluoride in Antarctic krill has been established. Four different pretreatment methods were used for the extraction of fluoride: double-deionised water extraction, sulphuric acid distillation, hydrochloric acid extraction, and pH adjustment with buffer after hydrochloric acid extraction. Four methods of comparative analysis revealed that sulphuric acid distillation was suitable preparation for ion chromatography determination of fluoride in Antarctic krill (flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In the melting point analysis of sodium diacetate, it was found that the melting point of the product was 95.6°C in accordance with the value from the reference 96°C [4] . From the above we can infer the product is sodium diacetate.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In the melting point analysis of sodium diacetate, it was found that the melting point of the product was 95.6°C in accordance with the value from the reference 96°C [4] . From the above we can infer the product is sodium diacetate.…”
supporting
confidence: 72%
“…[3] Reaction temperature can influence the sodium diacetate yield greatly in the total factors. [4] The optimum synthesis conditions for sodium diacetate are confirmed through the orthogonal test that reaction temperature is 70°C, reaction time is 60min, acetic acid-sodium hydroxide ratio is 2.1:1. The yield can reach to 96.2% under the best optimum synthesis conditions.…”
Section: Discussionmentioning
confidence: 94%
“…To determine fluoride concentrations, 1g of the grounded sample was incinerated with 8 g of mixture of carbonate potassium and carbonate sodium at 550 °C for 3 hours and digested with 50 ml of 1M hydrochloric acid (HCl) (Borjigin et al, 2009). All digested samples were analysed by potentiometry and ion chromatography (Metrohm, 850 Professional IC, Herisau, Switzerland) (Zhao et al, 2015).…”
Section: Plant Sampling and Chemical Analysismentioning
confidence: 99%